The influence of promotion and customer satisfaction on purchasing decisions for motorcycle products - Priyanto, Rofik; Filani, Libran; Setyaningrum, Tri; Arrizka, Davrina Fatkha (Institute of Computer Science (IOCS), 2025)
Purchasing decisions are the result of various factors, including promotion and customer satisfaction, which are important for the success of companies in the competitive automotive industry. This study aims to analyze the effect of promotion and customer satisfaction on purchasing decisions on motorcycle products at CV Kompo Motor Purbalingga. The research uses quantitative methods with data collection through questionnaires that have been tested for validity and reliability. The results of the analysis show that promotion and customer satisfaction have a significant and positive relationship to purchasing decisions, with customer satisfaction having a more dominant influence. The linear regression test shows a coefficient of determination of 65%, which indicates that the variability of purchasing decisions can be largely explained by the promotion and customer satisfaction variables. The implication of these findings is the importance of companies to develop promotional strategies that are aligned with improving service quality in order to increase customer satisfaction. However, this study has limitations on the scope of the research location, so further research is recommended to expand the scope of the study to other regions or industrial sectors to strengthen the generalization of the results.